Features of sinonasal hemangioma: A retrospective study of 31 cases. Issue 6 (December 2017) - Takaishi, Shinya; Asaka, Daiya; Nakayama, Tsuguhisa; Iimura, Jiro; Matsuwaki, Yoshinori; Hirooka, Shinichi; Takahashi, Hiroyuki; Kojima, Hiromi; Otori, Nobuyoshi
Abstract: Objective: Although hemangiomas are common lesions of the head and neck, sinonasal hemangiomas are rare. The purpose of this study was to analyze the clinical features (sex, age, symptoms, and size and anatomical location of the lesion) and the histological findings of sinonasal hemangioma cases, to assess preoperative transarterial embolization, and to evaluate the outcome (recurrence or no recurrence) of endoscopic sinus surgery. Methods: Clinical records of 31 patients who underwent endoscopic sinus surgery for resection of sinonasal hemangioma between January 2010 and June 2015 were retrospectively reviewed. Results: The study group consisted of 19 men and 12 women. Mean age was 53.3 ± 15.9 years. The principal symptom was epistaxis (81%). Mean tumor size was 12.6 ± 8.2 mm. The most common origin of hemangioma was the inferior turbinate (45%), followed by the nasal septum (39%), and, in both locations, the origin had a tendency to be located in the anterior portion. Thirty-one specimens were histologically categorized as 9 cavernous hemangiomas and 22 capillary hemangiomas. Preoperative transarterial embolization was performed in 2 cases. Only one recurrence was observed among 31 cases. In the recurrent case, the hemangioma of the nasal septum was resected during pregnancy. Conclusion: According to our results, the transnasal endoscopic approach can be useful for the resection of sinonasal hemangioma. However, sinonasal hemangioma in connection with pregnancy must be addressed with care to decide the appropriate time for treatment.